Pseudoexfoliation and Alzheimer's associated CLU risk variant, rs2279590, lies within an enhancer element and regulates CLU, EPHX2 and PTK2B gene expression. (26th August 2017) - Padhy, Biswajit; Hayat, Bushra; Nanda, Gargi Gouranga; Mohanty, Pranjya Paramita; Alone, Debasmita Pankaj
Abstract: Genetic variants at PTK2B–CLU locus pose as high-risk factors for many age-related disorders. However, the role of these variants in disease progression is less characterized. In this study, we aimed to investigate the functional significance of a clusterin intronic SNP, rs2279590, that has been associated with pseudoexfoliation, Alzheimer's disease (AD) and diabetes. We have previously shown that the alleles at rs2279590 differentially regulate clusterin ( CLU ) gene expression in lens capsule tissues. This polymorphism resides in an active regulatory region marked by H3K27Ac and DNase I hypersensitive site and is an eQTL for CLU expression. Here, we report the presence of an enhancer element in surrounding region of rs2279590. Deletion of a 115 bp intronic region flanking the rs2279590 variant through CRISPR-Cas9 genome editing in HEK293 cells demonstrated a decreased clusterin gene expression. Electrophoretic mobility shift and chromatin immunoprecipitation assays show that rs2279590 with allele 'A' constitutes a transcription factor binding site for heat shock factor-1 (HSF1) but not with allele 'G'. By binding to allele 'A', HSF1 abrogates the enhancer effect of the locus as validated by reporter assays. Interestingly, rs2279590 locus has a widespread enhancer effect on two nearby genes, protein tyrosine kinase 2 beta ( PTK2B ) and epoxide hydrolase-2 ( EPHX2 ); both of which have been previously associated with AD as risk factors. To summarize, our study unveils a mechanistic role of the common variant rs2279590 that can affect a variety of aging disorders by regulating the expression of a specific set of genes.